A technological innovation system approach to analysis knowledge spillover, the case of rotary-wing technology in Iran. Issue 4 (24th July 2020) - Miremadi, Tahereh; Baharloo, Mahdi
Abstract : Purpose: This paper aims to contribute to the debate of knowledge spillover by presenting a new application for the approach of the technological innovation system (TIS). Design/methodology/approach: Based on the evolutionary economics of the TIS approach, a new framework for knowledge spillover is built and applied to a case. To collect data in studying the case, a mix of quantitative–qualitative methods are used. Findings: TIS approach can help build a framework to analyze knowledge spillover from defense to the civil sector. This framework shows the direct relationship between the functional dynamics of the system and the spillover mechanism.. Research limitations/implications: Sharing the same weakness as TIS, the suggested framework does not pay attention to the contextual factors. Practical implications: This framework is an analytical tool. It could be used for educational and research purposes, but it has limited power to devise policy guidelines. Social implications: This framework is an analytical tool. It could be used for educational and research purposes. But it has limited power to devise policy guidelines. Originality/value: The paper deviates from the conventional literature of knowledge spillover which uses national level of system analysis. Based on TIS, it adds a new perspective to the literature which had suffered from a limited value of generalizability.